2011
DOI: 10.3892/mmr.2011.725
|View full text |Cite
|
Sign up to set email alerts
|

bFGF peptide combined with the pVAX-8CpG plasmid as adjuvant is a novel anticancer vaccine inducing effective immune responses against Lewis lung carcinoma

Abstract: Abstract. Due to the poor immunogenicity of subunit protein antigens, there is a need to use adjuvants in order to generate effective immune responses. Basic fibroblast growth factor (bFGF) is one of the best characterized pro-angiogenic cytokine and is a candidate target for anticancer therapy. We used truncated bFGF (tbFGF) combined with engineered pVAXnCpG as novel adjuvant to immunize mice in order to inhibit tumor angiogenesis and suppress tumor growth. In our study, the results demonstrated that the mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Antigenic peptide-human leukocyte antigen class I complex respond to cytotoxic CD8 + T-cells against malignant diseases and brain tumors ( 118 ). However, ACP-produced vaccines exhibit poor immunogenicity, and thus require adjuvants to increase specific immune responses ( 119 ). For example, E75 peptide breast cancer vaccine (Her2 p369-p377) containing polyactin A can increase CD4 + and CD8 + T lymphocytes, enhance proliferation of splenocytes and increase levels of interferon-γ in splenocytes ( 120 ).…”
Section: Classification Of Acpsmentioning
confidence: 99%
“…Antigenic peptide-human leukocyte antigen class I complex respond to cytotoxic CD8 + T-cells against malignant diseases and brain tumors ( 118 ). However, ACP-produced vaccines exhibit poor immunogenicity, and thus require adjuvants to increase specific immune responses ( 119 ). For example, E75 peptide breast cancer vaccine (Her2 p369-p377) containing polyactin A can increase CD4 + and CD8 + T lymphocytes, enhance proliferation of splenocytes and increase levels of interferon-γ in splenocytes ( 120 ).…”
Section: Classification Of Acpsmentioning
confidence: 99%
“…Studies utilizing recombinant protein vaccines targeting FGFR-1 demonstrated significantly decreased tumor volume compared to controls, as well as decreased microvessel density in tumors without any observable overt toxicity [ 49 ]. Peptide bFGF vaccines combined with adjuvants also induced antigen-specific antibody and cell-mediated responses [ 50 , 51 ]. Importantly, in a study where a liposome-based peptide bFGF vaccine was administered in murine cancer models, immunity against tumor endothelium was elicited while physiological angiogenesis was unperturbed, as evidenced by normal wound healing times and no impairments in the reproductive ability of vaccinated animals or in the viability or health of the offspring [ 52 ].…”
Section: Vaccines Targeting Defined Angiogenesis-associated Antigensmentioning
confidence: 99%